Experiences of mothers caring for children with schizophrenia in Vhembe District, South Africa - Negota, Azwihangwisi Josphinah (University of Limpopo (Turfloop Campus), 2013)
Mothers who care for schizophrenic children go through various personal experiences and face enormous challenges. The aim of the study was to explore the experiences of mothers whose children were diagnosed with childhood schizophrenia. Participants consisted of eight mothers of children with schizophrenia from a rural village in the district of Vhembe, South Africa. They were interviewed at their homes, using in-depth, phenomenological interviews. Eight themes emerged from the participating mothers‟ articulations. They were identified as poverty and unemployment, emotional reactions of mothers, blaming witchcraft, dealing with the children‟s violence, aggression and destructiveness, financial and social support, effect of schizophrenia on the mother-child relationship, and the loss that mothers go through. The study reconfirmed that caring for individuals with schizophrenia is not an easy task for mothers. Recommendations were advanced on the basis of the findings. Keywords: caregiving, children, expressed emotion, objective burden, parenting, phenomenology, schizophrenia, subjective burden
Thesis (M.A. (Research Psychology)) --University of Limpopo, 2013
Keywords: Parenting; Childhood chizophrenia; 362.62; Schizophrenia; Schizophrenia in children